Governing (Socio)Materialities at the Intersection of STS and Internet Governance: Hybridization as a Product of Necessity - Fratini, Samuele (Tecnoscienza – Italian Journal of Science & Technology Studies, 2025)
In the last years, a rich literature has emerged at the intersection of Internet Governance as a field of study and Science and Technologies Studies. This Scenario retraces the complex social and technical historical developments that favored the integration of these two fields. This hybridization process can be described as a “product of necessity” – a descriptive label highlighting how the integration of STS concepts responded to evolving analytical challenges. It is delineated through a reconstruction in three phases, whose aim is to describe key intersections and to capture the ongoing trends within the Internet Governance community. The analysis shows that the first “turn to infrastructure” (Bowker et al. 2010) in the 2010s oriented scholarly interest towards materialities and protocols of the Internet as information infrastructure, thus favoring the study of its “control points” (Musiani et al. 2016). On the other hand, today’s focus on geopolitical competition and informal governance practices provokes renewed interest in the social and situated components of the Internet infrastructure, such as imaginaries, contestations, and reappropriations. The Scenario finally discusses possible future approaches and research interests.